"Monica and Friends": the challenge to internationalize. Issue 2 (22nd June 2017) - de Aguillar Pinho, Maria Luiza Carvalho; da Rocha, Angela Maria Cavalcanti; de Aguillar Pinho, Celso Roberto; Giovannini, Cristiane Junqueira
Abstract : Subject area: International business or International marketing. Study level/applicability: The case is recommended for undergraduate and graduate courses in the fields of international business and international marketing. The aim is to show students the problems that a family business in the animation industry faces while growing and internationalizing. Specifically, the case discusses the entry mode selection and market selection challenges faced by an emerging market company in the comic book and animation industry to operate overseas and compete with entertainment giants such as Disney and DC Comics. The case enables the instructor to discuss international market selection theories and evaluate entry modes. For graduate students, the international market selection can be further developed by using more robust concepts such as psychic and cultural distance. Case overview: This case examines the trajectory of a pioneering company in the comic book and animation industries, and in the licensing of trademarks in Brazil. Mauricio de Sousa Productions was founded in 1959 and is considered to be one of the most successful cultural producers in the country. According to a leading Brazilian public opinion research agency, 97 per cent of Brazilian children and 96 per cent of their parents are familiar with the Monica and Friends characters. As one of the main players in the publishing market, with 86 per cent of market share, Mauricio de Sousa Productions has a product portfolio that goes beyond Monica and Friends comic strips: the company's show on the Cartoon Network ranks third in audience viewing in the country and the company has produced animated movies, books, shows and games. However, despite its experience in publishing comic books in several countries, Mauricio de Sousa Productions (MSP)'s worldwide operations have not been as profitable and sustainable as expected. Aiming at expanding its global presence, MSP's top management decided in 2014 to review the company's internationalization strategy and operations to enhance the firm's performance. Expected learning outcomes: The case highlights the key factors facing firms when expanding from an emerging markets. Students are expected to discuss and evaluate options, thus developing their knowledge and decision processes related to family-owned business challenges and opportunities, international market selection theories and international market entry mode. Developing strategies to face challenges as those presented by competitors such as Disney should bring opportunities to students to think outside models and weigh risks. Finally, the case gives students opportunity to base their decision processes and evaluations on logistics problems as well as psychic and cultural distances. It also compels the students to appreciate the various challenges involved in exploiting international market with animation content and intellectual properties as a service. Supplementary materials: Company presentation to use in the discussion introduction can be found in: www.monicaandfriends.com/content/video.php Subject code: CSS 5: International business.